Gender Identity Crisis in the Urban Kitchen - Şimşek, Burcu; İnce, Şengül (2017)
In the context of gender roles, this paper raises questions concerning the entrance of middle class men into the kitchen that is usually associated as a place that belongs to women and in these cases how the relationship between woman and man is effected in Turkey. In-depth interviews were held with five middle class couples living in Ankara in their own kitchens. Carrying out the interviews in the couples’ own kitchens gave us the opportunity to observe their relationship to the kitchen as well as their behaviours in the kitchen. At the end of this study, it is likely to point to the change in the meaning and state of the kitchen in addition to which we talk about the shift in the meaning from preparation of food as part of biological necessity to emphasis on life style with the entrance of men into the kitchen. Women are not always happy about men’s ownership of the kitchen on the other hand.